The reproductive cycle of a holothuriid sea cucumber (Holothuroidea Aspidochirota), Holothuria (Bohadschia) marmorata marmorata jaeger. - Chavez, Mary Libertine Bolivar (1986.)
Mangroves are vital to both marine and coastal ecosystems. The oil spill incident last August 11, 2006, has apparently damaged the vast mangrove community in TINMAR. The leaves of mangrove species, namely Rhizophora apiculata, Rhizophora stylosa, Rhizophora mucronata, Sonneratia alba and Avicennia marina gathered from six sampling sites were analyzed for copper, lead, nickel and zinc heavy metals. heavy metal levels in leaves were correlated with levels in sediments. Sample preparation of leaves and sediments was done by employing the Hotplate Acid digestion Method prescribed by the Association of Official Analytical Chemists (AOAC). Heavy metal analysis was carried out by using the Flame Atomic Absorption Spectrophotometer (Varian SpectraAA 55B). Data gathered were subjected to statistical analyses by using the following statistical tools: One-Way ANOVA. Duncan's Multiple Range Test and Pearson product-Moment Correlation., The results of this study show that the concentrations of copper, lead nickel and zinc in the leaves of R. apiculata, R. stylosa, R. mucronata, S. alba and A. marina vary in the six sampling sites. Variations are likely due to different environmental conditions that influence physiological processes of the individual species in different sites. Additionally, mean metal concentration of copper, lead nickel and zinc are within safe limits. the results also show that the concentrations of copper , lead, nickel and zinc in the sediments vary in the six sampling sites. Dissimilarities are likely influenced by varying environmental condtions such as pH, redox potential organic matter content and sulfide content of sediments; which , as a result determine the sorption and/or bioavailability of metals. In addition, mean metal concentration of copper, lead nickel and zinc are within safe limits. Furthermore, it was also found that there is no correlation between metal concentration: (a) in the leaves of each of the five species in the oiled sites and in the leaves of the same species in the unoiled site; (b) in sediments in the oiled sites and in sediments in the unoiled site and; (c) in mangrove leaves and in sediments in both oiled and unoiled sites. This study also found that copper level in mangrove leaves increased from October 2007 to October 2008; while lead and nickel levels in mangrove leaves decreased over time and zinc level remained essentially the same. Likewise, copper and zinc levels in sediments increased while lead and nickel levels remained the same over time.
Research Paper (Undergraduate, Bachelor of Science in Natural Sciences) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Sea cucumber; Holothuroidea: aspidochirota